The effect of 4.3 GHz high-power microwave exposure on human corneal epithelial cells - Gao, Anning; Zhao, Xuelong; Wu, Shuang; Liu, Xiaoman; Wang, Xinyu; Tan, Luhao; Li, Zhihui; Dong, Guofu; Wang, Changzhen (Frontiers in Cell and Developmental Biology, 2026)
IntroductionHigh-power microwave (HPM) exposure can produce biological effects in cells, but the specific characteristics and mechanisms of these effects in ocular tissues remain poorly defined. This study aimed to investigate the biological responses of human corneal epithelial cells (HCE-T) to 4.3 GHz HPM exposure, with a focus on moderate-dose effects.MethodsHCE-T cells were exposed to 4.3 GHz HPM at average specific absorption rates (SARs) of 1.64, 3.28, and 8.2 W/kg. Cellular responses were evaluated by measuring cell viability, reactive oxygen species (ROS) generation, mitochondrial membrane potential, and apoptosis at multiple time points. Transcriptomic analysis was performed to identify underlying molecular pathways.ResultsModerate-dose exposure (3.28 W/kg) resulted in the most pronounced cellular effects, including early and significant ROS elevation, marked collapse of mitochondrial membrane potential, the highest apoptosis rate, and sustained inhibition of proliferation. Transcriptomic profiling showed strong suppression of the mTOR signaling pathway, upregulation of TSC2, and activation of Polycomb-mediated chromatin remodeling, suggestive of autophagy induction and irreversible cell cycle arrest. In contrast, low-dose exposure (1.64 W/kg) primarily activated DNA repair and adaptive pathways, while high-dose exposure (8.2 W/kg) predominantly disrupted metabolic and membrane signaling with a trend toward recovery.DiscussionThese findings demonstrate that moderate-dose 4.3 GHz HPM exposure induces a uniquely strong stress response in HCE-T cells, characterized by oxidative stress, mitochondrial dysfunction, and activation of stress-related signaling pathways. These results highlight the importance of considering specific exposure conditions in assessing HPM bioeffects and ocular safety.